PETA PIKIRAN SEBAGAI APERSEPSI DARI ABSTRAK KE KONKRET MENUJU KEBERMAKNAAN BELAJAR - Aly Mahfud (BASA Journal of Language & Literature, 2021)
Abstract: Bringing meaning to learning is one of the core of teaching. To achieve that, it is necessary to bring meaningfulness in learning, namely to associate learning materials with natural reality by learners and to focus on usefulness. That way, learning can be accepted by students. One of the things Ausabel emphasizes is to give a firm hook in learning to turn abstracts into concrete. A mind map as an aperception is an idea that qualifies for the benefits of learning. This study uses the design of literature research to answer (1) how important is the aperception in meaningful learning? and (2) how is the mind map used as the main activity in aperception when starting learning to realize meaningful learning? with the design of literature research, the research answer is obtained as follows: (1) The aperception is important in the initial learning activities as a hook between new topics and the experience of previous learners. as well as the usefulness of the topic with real life. (2) the mind map as an aperception facilitates learners to relate their experiences and get an explanation of material usefulness for themselves. These two main points are in accordance with Ausabel's goal of developing meaningful learning theory. Keywords: mind map, aperception,, abstract, concrete, meaningful learning